Detection and assessment of cardiac patent foramen ovale - Parlak, İsmail Burak. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2013., 2013)
Arterial microemboli are gas lled structures which are formed in intravascular and extravascular environment. They are characterized in spherical or ellipsoid forms which would cause diseases in a broad range from stroke to migraine. Cardiac Patent Foramen Ovale (CPFO) is considered as a congenital defect through both atria as a permeable shunt with a prevalence frequency of 25-30% in asymptomatic population. Decompression Sickness (DCS) is a fatal disease during hyperbaric and hypobaric activities due to unestimated e ects of microemboli. CPFO aperture combined with DCS is a clinical problem where bubble analysis is managed manually by special and trained cardiologists. Even this problem was considered recently by di erent groups within sound, image and video forms, an automated tool is considered as a challenge due to algorithmic and mechanical constraints related to noise, monitoring and probe localization. We aimed to develop a spatio-temporal methodology for clinicians which would not carry out long lasting videos where the number and the size of microemboli alter dynamically. In this thesis, developed methods are classi ed into two groups; qualitative and quantitative assessments. These approaches were tested initially in a simulation environment with arti cial microemboli. Furthermore, microemboli and CPFO were monitored in subjects through videos using two modalities: contrast Trans Esophageal Echocardiography and contrast Trans Thoracic Echocardiography. Even our procedures would get accurate ndings within videos, it is important to note that low resolution, high speckle noise, shadowing would introduce false alarms. Consequently, we conclude that this routine would standardize CPFO analysis and o er better adjustment for bubble detection.|Keywords : Congenital Defect, Intravascular Microemboli, Right-to-Left Shunts, Gabor Wavelet, Active Contours, Decompression Sickness.
Keywords: Cardiology.; Cardiac catheterization.; Abnormalities, Human.